"Just because I don't bleed, doesn't mean I don't go through it": Expanding knowledge on trans and non-binary menstruators. Issue 1 (30th September 2020) - Lowik, A.J.
Abstract: Objectives: Critical menstruation studies is a field in its nascence, marginalized within the broader area of reproductive health research. Menstruation-related research is virtually absent from trans studies, itself a marginalized field of inquiry. This article focuses on the experiences of trans and non-binary menstruators, to contribute to this burgeoning area of study. Methods: This article involves secondary data analysis of a qualitative dissertation research study on trans people's reproductive lives, health, and decision-making processes. Of the fourteen participants in the broader study, eleven discussed their perceptions of and experiences with menstruation and menstrual health. Those experiences where subjected to thematic narrative analysis, with a focus on themes that were substantively significant. Results: Participants describe experiences with amenorrhea associated with the use of testosterone, menstrual resumption following the cessation of testosterone and for other reasons, menstruation-related dysphoria management strategies beyond medical interventions, as well as barriers to menstruation-related health care. One participant describes bloodless periods as a trans woman, a phenomenon altogether absent from the clinical and experiential literature in this field. The article explores how cisnormativity, repronormativity and transnormativity informed the participants experiences of menstruation and reproductive health care. Conclusions: Contributing novel stories to the literature, this article illustrates how clinically focused research fails to attend to the experiential components of menstruation for trans and non-binary people. Expanded knowledge is beneficial to the development of gender-inclusive menstruation research, clinical interventions, healthcare environments, and activist efforts.